Service Learning: A Study of Relevancy in Nepal - Karki, Dataram (KMC Research Journal, 2019)
Service learning is one of the lately introduced curriculum as well as method of teaching in the world. In practice, it is applicable in both school and higher level. The curriculum is partial one which is made based on students’ direct participation in community. The theory of service learning is basically learning through experience. Many education provider institutions around the world have developed it as mandatory curriculum with objective of making students active and community friendly. The relevancy of the curriculum corresponds with ultimate objective of education. The offered curriculum can have insight to strengthen reciprocal relation between students and society, and let them know about society, knowledge and social issues. As such direct involvement of students in community changes their perspectives toward society and nation.